Digital-Based Archives Management Training For Sub-District Employees and Village Appliances In The Telaga Jaya District, Gorontalo Regency - Tune Sumar, Warni; Abdul Radjak, Intan; Lamatenggo, Nina (Devotion : Journal of Research and Community Service, 2022)
Telaga Jaya Sub-district is one of the sub-districts in the Gorontalo Regency which consists of 5 villages namely: Bulota Village, Buhu Village, Bunggalo Village, Luwooo Village and Hutadaa Village whose area conditions are in flood-prone areas need to be aware of various possible flood disasters that can occur. can destroy residential residents and government offices. One of the important assets to be saved before being hit by a flood disaster is assets in the form of archives in government offices. Implementation Method The method of implementing the activity is to provide an understanding of the management and storage of archives manually and digitally. Submission of material is carried out by resource persons and lecturers who are members of the team proposing community service activities. In addition, activities in the context of community service use two methods, namely 1) Lectures or counseling. In this method, lecturers or extension workers deliver material about Introduction to Archives and Digital Archives Training. On that occasion the participants were freed to ask questions with the material giver. The details of this method are an explanation of how to manage archives with a digital system. 2) Interactive dialogue, in this case participants are positioned as subjects who can provide reviews related to problems in archive management. This dialogue serves as brainstorming from participants to obtain input in the form of problems, aspirations, proposals, ideas and solutions. 3) The distribution of questionnaires before and after the implementation of the counseling (pretest and posttest questionnaires). The purpose of distributing this questionnaire is to get a comparison of participants' knowledge and insights about Archive Management.